Saving Mungo Park - Nwelue, Onyeka (Nigeria, 2021)
Ulamma is a widow. She lives with her two children, Ike and Ada. Ike and Ada are twins. They look very much like each other and they like almost the same things too. Ulamma has a lot of farmlands. She grows cocoyams and vegetables. She also owns a plantation of palm trees. Everyone says she is a very hardworking woman, and they like her for this. One day, she sees a man, whose skin was very pale and his hair was long and had the colour of corn cobs that had been left for too long in the fields, lying helplessly by River Niger. And that was Mungo Park...
Keywords: Adventure; Historical; Juvenile Fiction; Mungo Park